Effects of Vibration Therapy on Immobilization-Induced Hypersensitivity in Rats. Issue 7 (1st July 2015) - Hamaue, Yohei; Nakano, Jiro; Sekino, Yuki; Chuganji, Sayaka; Sakamoto, Junya; Yoshimura, Toshiro; Okita, Minoru; Origuchi, Tomoki
Abstract : Background: Cast immobilization induces mechanical hypersensitivity, which disturbs rehabilitation. Although vibration therapy can reduce various types of pain, whether vibration reduces immobilization-induced hypersensitivity remains unclear. Objective: The purpose of this study was to investigate the preventive and therapeutic effects of vibration therapy on immobilization-induced hypersensitivity. Design: The experimental design of the study involved conducting behavioral, histological, and immunohistochemical studies in model rats. Methods: Thirty-five Wistar rats (8 weeks old, all male) were used. The right ankle joints of 30 rats were immobilized by plaster cast for 8 weeks, and 5 rats were used as controls. The immobilized rats were divided randomly into the following 3 groups: (1) immobilization-only group (Im, n=10); (2) vibration therapy group 1, for which vibration therapy was initiated immediately after the onset of immobilization (Im+Vib1, n=10); and (3) vibration therapy group 2, for which vibration therapy was initiated 4 weeks after the onset of immobilization (Im+Vib2, n=10). Vibration was applied to the hind paw. The mechanical hypersensitivity and epidermal thickness of the hind paw skin were measured. To investigate central sensitization, calcitonin gene-related peptide (CGRP) expression in the spinal cord and dorsal root ganglion (DRG) was analyzed. Results: Immobilization-induced hypersensitivity was inhibited in the Im+Vib1 group but not in the Im+Vib2 group. Central sensitization, which was indicated by increases in CGRP expression in the spinal cord and the size of the area of CGRP-positive neurons in the DRG, was inhibited in only the Im+Vib1 group. Epidermal thickness was not affected by vibration stimulation. Limitations: A limitation of this study is that the results were limited to an animal model and cannot be generalized to humans. Conclusions: The data suggest that initiation of vibration therapy in the early phase of immobilization may inhibit the development of immobilization-induced hypersensitivity.